Ancient Egyptian Image-Writing: Between the Unspoken and Visual Poetics - Rashwan, Hany.
This article highlights the significance of considering the visual mediums of the ancient Egyptian (henceforth AE) writing system, in reading and translating AE literary texts. Despite their importance for understanding the internal mechanism of AE literary expressions, modern scholarship has not assimilated these visual mediums into its exploration. A possible theoretical framework for AE morphology structure may identify two input systems,, one visual for visually presented materials that are more related to visual comprehension, and the other phonological for material presented using the auditory modality. The studied examples confirm that the AE writers had the opportunity to invite their receivers to take part in two experiential tasks (visual and phonological) to provoke two different behaviours, to get the right meaning intended by the resourceful writer. The article is divided into two parts. The first part is concerned with the role of innovative imagination in forming both the “eloquent content” and its inseparable “poetic vocal form,” with full consideration of the creative relationship between these two elements. The second part is related to the ancient and modern reader’s reception of such visual-verbal interactions. The article demonstrates the significance of looking into such visual aesthetics—which were mainly designed to stimulate the eyes of the indigenous readers—to shape any theory related to the literary nature of ancient Egyptian writing. http://dx.doi.org/10.5913/jarce.55.2019.a009